Multi-analyte Electrochemical Sensor Platform for Simultaneous Measurement of Inflammatory Airway Disease Biomarkers - Nadia Moukri; Federico Massaro; Bernardo Patella; Giuseppe Aiello; Chiara Cipollina; Elisabetta Pace; Rosalinda Inguanta (Chemical Engineering Transactions)
Asthma and Chronic Obstructive Pulmonary Disease are two widespread chronic inflammatory lung diseases. Asthma impacts approximately 300 million people worldwide, while COPD is the fourth leading cause of death globally. Monitoring these diseases progression through biomarker measurements could be crucial to improve disease management and create personalized treatments. Furthermore, detecting multiple biomarkers quickly and directly in situ can significantly improve the knowledge of airway diseases using cell culture models that replicate airway tissues. For this aim, in this work a novel multianalyte sensor platform was fabricated using laser scribing, for highly sensitive detection of H2O2, and pH levels chosen as biomarkers due to their significant role in lung damage during inflammation. Electrochemical methods offer the opportunity to perform rapid, simple, and accurate analysis. The sensor design consists of two working electrodes and integrated counter and Ag/AgCl reference electrodes. The electrode for H2O2 detection was modified with reduced graphene oxide and gold nanoparticles, while the pH electrode was modified with the conductive polymer Polyaniline. The sensors detected accurately and sensitively all two analytes demonstrating excellent performance in phosphate buffer. Linear scan voltammetry was utilized for the detection of H2O2, and potentiometry was used for pH level measuring. This approach demonstrated the sensors efficacy in analysing multiple analytes simultaneously.